STRATEGI BADAN NARKOTIKA NASIONAL KOTA PEKANBARU DALAM PENANGGULANGAN PENYALAHGUNAAN NARKOBA - Jefri Sidik; Geovani Meiwanda (Pusat Riset dan Inovasi Nasional, 2022)
This research is motivated by the rise of drug abuse cases, especially in Pekanbaru City which can damage themselves and others. The increasing number of drug abuse cases has become a special concern for the Government and also the people in Pekanbaru City. The existence of a strategy designed by the Pekanbaru City National Narcotics Agency (BNNK) to tackle drug abuse is expected to be able to overcome drug problems in accordance with the provisions of Law No. 35 of 2009 concerning Narcotics. This study uses qualitative research methods with data collection techniques through interviews and documentation. This study aims to obtain data on the strategy for overcoming drug abuse by the Pekanbaru City National Narcotics Agency (BNNK) and the factors that inhibit it. The results of this study indicate that the drug abuse prevention strategy designed by the Pekanbaru City National Narcotics Agency (BNNK) has not fully worked as expected, so that drug abuse cases have not been significantly reduced. This is due to the inhibiting factors, namely the lack of availability of human resources and limited supporting tools.